Search This Blog

Brain Twister Puzzle

Brain Twister Puzzle Solution - 28 july

2+3=8,
3+7=27,
4+5=32,
5+8=60,
6+7=72,
7+8=??

Solve it?

1. (a*(a+b))-a

1. Your are the real genius.

2. It's "You're the real genius"

3. wow but try to solve 84*[2+2+2]!.

4. in other way it can be solved as a*(b+(a-1))

5. This comment has been removed by the author.

6. (a-1)(a+b)+b

7. (a * b) + (a * (a-1))
(7 * 8) + (7 * 6) = 98

8. its 98
2*(3+1)=8
3*(7+2)=27
4*(5+3)=32
5*(8+4)=60
6*(7+5)=72
7*(8+6)=98

9. 2*1+(2*3)=8
3*2+(3*7)=21
4*3+(4*5)=32
5*4+(8*5)=60
6*5+(7*6)=72
7*6+(8*7)=98

10. (2*3)+2=8
(3*7)+6=27 (:6-2=4)
(4*5)+12=32 (:12-6=6)
(5*8)+20=60 (:20-12=8)
(6*7)+30=72 (:30-20=10)
(7*8)+42=98 (:42-30=12)

11. Siddaram S I
2*3=6(+2=0+2)
3*7=21(+6=2+4)
4*5=20(+12=6+6)
5*8=40(+20=12+8)
6*7=42(+30=20+10)
7*8=56(+42=30+12)

12. ∑ c(n-1)+d(n) - (∑ c(n-1)+d(n) - ∑ a(n-1)+b(n)) = u
n = 2 n = 3

2(1) + 3(2) = 8 = u
3(2) + 7(3) = 27
4(3) + 5(4) = 32
5(4) + 8(5) = 60
6(5) + 7(6) = 72
7(6) + 8(7) = 98

13. Steve Jobs

Thought exactly like that, although without this part:

"∑ c(n-1)+d(n) - (∑ c(n-1)+d(n) - ∑ a(n-1)+b(n)) = u
n = 2 n = 3"

... I'm just inthe 9th grade (from Portugal).

14. Its 98

then multiply the result with first number
and then subtract the first number with the result

therefore: 7+8 = 15
then 15 X 7 = 105
then 105 - 7 = 98

15. Answer is 98.. this is how we get:
[2]+3=8............... 2*3+2 (2 is the initial product)
[3]+7=27............. 3*7+6 (2*3)
[4]+5=32............. 4*5+12 (4*3)
[5]+8=60............. 5*8+20 (5*4)
[6]+7=32............. 6*7+30 (6*5)
[7]+8=32............. 7*8+42 (7*6)

Rule: Multiply both numbers and add a [NUMBER]

this Number is found by multiplying the first number of the row with the previews number respectively, shown in square brackets.

16. (2*1) + (3*2) = 8
(3*2) + (7*3) = 27
(4*3) + (5*4) = 32
(5*4) + (8*5) = 60
(6*5) + (7*6) = 72
(7*6) + (8*7) = 98

1. yes < because 9de-shift0
@89#=!0+*<
#89&=@0+@&<
\$89%=#0+#@<
%89*=\$0+^)<
^89&=%0+&@<
&89*=^0+(*>

2. A*b + a*(a-1)
Or
A*(a+b-1)
Or
A*a + a*b -a

3. 2*(3+1)=4
3*(7+2)=27,
4*(5+3)=32,
5*(8+4)=60,
6*(7+5)=72,
7*(8+6)=98

1. 2*(3+1)=4
3*(7+2)=27,
4*(5+3)=32,
5*(8+4)=60,
6*(7+5)=72,
7*(8+6)=98

4. a+b=c
c/a=d
d=a+b-1
7+8=15;15-1=14;14*7=98
7+8=98

5. ans is 98...
(2*3)+2 = 8
(3*7)+6 = 27
(4*5)+12 = 32
5*8 + 20 = 60
6*7 + 30 = 72
7*8 + 42 = 98

1. I still did not get it!
:(

6. 2+3=5
5*2=10
10-2=8

3+7=10
10*3=30
30-3=27

similarly
7+8=15
15*7=105
105-7=98

7. A+B=C
D+E=F

Rule: F = ((D+E)*A) + E

Thus, ans is 98.

-Manoranjan

8. nice
by sowmya

9. Wrong the answer is 98 try to analyze the problem.... you will still get the correct answer.....

10. (2*3)+(2*1)=8
(3*7)+(3*2)=27
(4*5)+(4*3)=32
(5*8)+(5*4)=60
(6*7)+(6*5)=72
(7*8)+(7*6)=98

11. a-3=45*9/9-9+102=a
a*2=a
a*a=3
8*8=64a+a=3
3*3=9+a=a
this is the awnser 4 sure cause i know alot about math i know it all for this math problem for the harest and easyest cause this is a*a=3 then8*8=64cause if you add subtract divide multiply you get the problem and awnser ther is the awnser to the math problem this is realy easy because it is all in your bloode and brain i have the right awnser.......Thank you for reading this

12. = (b+o) * a where
b = 2nd number
o = order that the equation appears in or (a-1)
a = first number

13. 1*a+2*b
2*a+3*b
3*a+4*b
4*a+5*b
and so on.......

14. 1*(2+3)+3=8
2*(2+7)+7=27
3*(2+5)+5=32
4*(2+8)+8=60
5*(2+7)+7=72
6*(2+8)+8=98

15. Super..........

16. fantastic

17. I LIKED IT

18. a(a+b-1)
2(2+3-1)=8
3(3+7-1)=27
4(4+5-1)=32
5(5+8-1)=60
6(6+7-1)=72
7(7+8-1)=98

19. 2*1 + 3*2 = 8
3*2 + 7*3 = 27
4*3 + 5*4 = 32
5*4 + 8*5 = 60
6*5 + 7*6 = 72
7*6 + 8*7 = 98

Explanation:
Here, 2+3=2*(3+1)= 8
3+7=3*(7+2)= 27,
4+5=4*(5+3)= 32,
5+8=5*(8+4)= 60,
6+7= 6*(7+5)= 72,
Therefore,
7+8= 7*(8+6)=98

21. 2*1+3*2=8
3*2+7*3=27
4*3+5*4=32
5*4+8*5=60
6*5+7*6=72
7*6+8*7=98

22. selvakumar (a+b)-1*a

the formula is :
(a+b)(a-1)+b
simplified to :
a(a+b-1)
I enjoyed it!

24. nice question i got the answer 98

25. x * (x + y - 1), so 98

26. 98.
This should have been rated as an easy puzzle.

27. 2+3=8,
3+7=27,
4+5=32,
5+8=60,
6+7=72,
7+8=??

(2+3)*2- 2=8
(3+7)*3-3=27
(5+8)*5-5=60
(7+8)*7-7=98

28. 2+3=8,
3+7=27,
4+5=32,
5+8=60,
6+7=72,
7+8=??

(2+3)*2- 2=8
(3+7)*3-3=27
(5+8)*5-5=60
(7+8)*7-7=98

29. 98

the solution is,

a*(a+b-1)
example-
if 7=a
and 8=b
then solution is
7*(7+8-1) = 7*14 = 98

30. 98
2*3+2
3*7+6
4*5+12
5*8+20
6*7+30
7*8+42

31. This comment has been removed by the author.

32. 98 is right answer for without any formula we can think logically

33. ans is 106
n(a)+m(b);n=1,2,3,4,5,6
;m=2,3,4,5,6,7

2+3=5-1=4*2=8
3+7=10-1=9*3=27
4+5=9-1=8*4=32
5+8=13-1=12*5=60
6+7=13-1=12*6=72
7+8=15-1=14*7=98
Sunil kumar

35. ((a-1)*(a+b))+b

36. (a*a)+((a*b)-a)

37. ANS:98

38. Ans: 98

A*B + A * (A-1)

39. ans.98
b+a*a-a
8+7*7-7
15*7-7
105-7
98

40. Ans : 98

Logic:
2*(3+1)=8
3*(7+2)=27
4*(5+3)=32
5*(8+4)=60
6*(7+5)=72
7*(8+6)=98

41. The ans is 98

42. it's wrong

43. one more solution :
2*3+(2)=8
7*3+(2+4)=27
4*5+(2+4+6)=32
5*8+(2+4+6+8)=60
6*7+(2+4+6+8+10)=72
7*8+(2+4+6+8+10+12)=108

Ans: 108

44. x+y = x*y + x(x-1)
so
7+8 => 56 + 42 => 98

45. (ab)+(a(a-1))=R

Though I don't feel any accomplishement for finding an answer in less than 10 mins. Random pattern finding is what solves these type of problems.

46. 98, (a+b)*n+b , where n is the sequence no of equation.

47. 2 + 3 = 8 : 2* (2+3-1)
3 + 7 = 27 : 3* (3+7-1)
.
.
7+ 8 = 98 : 7*(7+8-1)

48. 2*(3+1)=8
3*(7+2)=27
.
.
.
7+(8+6)=??? = 98

49. a*b+(a-1)*a....

50. 98 that's quite simple

52. {(a*b)+i*a},where i=1,2,3....

53. 98
bcoz
2+3=2*[3+(2-1)=8
3+7=3*[7+(3-1)=27
4+5=4*[5+(4-1)=32
5+8=5*[8+(5-1)=60
6+7=6*[7+(6-1)=72
Therefore
7+8=7*[8+(7-1)]=98
x+y=x[y+(x-1)=x^2+xy-x

54. since when 2+3=8? this is a wrong equality from the very beginning and against all math theories. 2+3=5 and therefore 7+8=15

55. 2 * 3 + 2 =8
3 * 7 + 6 =27,
4 * 5 + 12 =32,
5 * 8 + 20 =60,
6 * 7 + 30 =72,
7 * 8 + 42 = 98

56. you guys are smart..

57. There are lots of solutions to this. One set is of the form:
f(x,y)=(1-n)x^2-2ny^2+(3n+1)xy-(12n+1)x+13ny+11n
where n=0,1,2,3,...
if n=0 then f(x,y)=x^2+xy-x which produces f(7,8)=98
if n=1 then f(x,y)=-2y^2+4xy-13x+13y+11 so f(7,8)=120
continue to get 142,164, 186,....

58. this is the way i solved it.....
first i try to find the common pattern
2,3=8 (8/2=4) and 2+3 =5 that means 4,5
3,7=27 9,10
4,5=32 8,9
5,8=60 12,13
6,7=72 12,13
7,8 =98 14,15 in this case i first find 7+8 =15,,and 15-1=14,,,,then 14*7......98......

59. Poor notation ... any maths teacher writing 2+3=8 should be flayed alive. '+' has a well-defined meaning, it means 'add'. That is not what you are doing here, so you must not use '+'.

You could either write it as 2*3=8 (although in type, you have to make it clear that that is not a multiplication sign), or more correctly f(2,3)=8.

60. Simplest formula:
a(a+b-1)
7*(7+8-1) = 98

61. as per my logic..the second number has been added with 1 and multiplied with previous one ....similarly in second case second no is added with 2 and multiplied with first one...so on...so the answer is 53 ...it too works

1. sorry sory..its 98..7*(8+6)

62. 98
I got it and I'm in 5th grade

63. I actually did this a different way. (Perhaps it is algebraically equivalent, but my homework is more important than proving this).

If you multiply each set of two numbers together, and subtract their answers, they form a sequence, in which the next term is 98.
The sequence is:
2,6,12,20,30, T
Note that each time the difference increases by 2, from 4 to 6, to 8 and so on.
This implies that the difference between 30 and t should be 12 and that T = 42. If we add T to the product of 7 and 8 (56) we end up with 98, as per the solution.

I thought that was fun, anyway.

L.

64. (a-1)*a+a*b:

(2-1)*2+2*3 = 8
(3-1)*3+3*7 = 27
(4-1)*4+4*5 = 32
(5-1)*5+5*8 = 60
(6-1)*6+6*7 = 72
(7-1)*7+7*8 = 98

65. The logic used is, a+(a+1)=(a*(a+1))+a(a-1). Therefore the answer is 98

66. It will solve by this Eqn
a²+ab-b

a= 1st term
b= 2nd term

67. It will solve by this Eqn
a²+ab-b

a= 1st term
b= 2nd term

68. It's 98. Did a cheating and solved using genetic programming. :)
Ans = (x + y -1) * x

69. (6*7) + (7*8) = 42 + 56 = 98

70. Good question for IQ test

71. Good question for IQ test